2003
DOI: 10.1074/jbc.m300757200
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Human Myosin III as a Motor Protein Having a Protein Kinase Activity

Abstract: The class III myosin is the most divergent member of the myosin superfamily, having a domain with homology to a protein kinase. However, the function of class III myosin at a molecular level is not known at all, and it has been questioned whether it is actually an actinbased motor molecule. Here, we showed that human myosin III has an ATPase activity that is significantly activated by actin (20-fold) with K actin of 112 M and V max of 0.34 s ؊1 , indicating the mechanoenzymatic activity of myosin III. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 54 publications
6
50
2
1
Order By: Relevance
“…NINAC would be predicted to be required only for movement into the rhabdomeres, since it may be a plus-enddirected motor, based on analyses of a mammalian myosin III [190][191][192], and the barbed ends of the actin filaments are at the distal end of the rhabdomeres [193]. Consistent with this proposal, NINAC is required for translocation of the Gα q and Arr2 from the cell bodies to the rhabdomeres, but not for the movement out of the rhabdomeres [183,189].…”
Section: Long-term Adaptation Through Light-dependent Translocation Omentioning
confidence: 92%
“…NINAC would be predicted to be required only for movement into the rhabdomeres, since it may be a plus-enddirected motor, based on analyses of a mammalian myosin III [190][191][192], and the barbed ends of the actin filaments are at the distal end of the rhabdomeres [193]. Consistent with this proposal, NINAC is required for translocation of the Gα q and Arr2 from the cell bodies to the rhabdomeres, but not for the movement out of the rhabdomeres [183,189].…”
Section: Long-term Adaptation Through Light-dependent Translocation Omentioning
confidence: 92%
“…Phosphorylation Sites in the Kinase Domain and Kinase Regulation-Our work and the work of others have demonstrated that class III myosins are capable of autophosphorylation (3,21,23,24,36). In this work, we determined the phosphorylation sites in the motor and kinase domain by mass spectrometry with and without undergoing in vitro autophosphorylation (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…NINAC has been suggested to play a role in phototransduction (Porter et al, 1992;Wes et al, 1999a) as well as in linking the axial cytoskeleton to the microvillar membrane (Hicks et al, 1996;Hicks and Williams, 1992). Although mechanoenzymatic activity has not yet been demonstrated for Drosophila NINAC, a recent report by Komaba et al (Komaba et al, 2003) showed that human myosin III functions as an actin-based motor protein with a translocating activity of 0.11 µm second -1 , as determined in an in vitro actin gliding assay. Because human myosin III acts as a plus-end motor (Komaba et al, 2003) and microvilli consist of bundled actin filaments polarized with their plus ends oriented away from the cell body (Arikawa et al, 1990;Mooseker et al, 1982), we expected that NINAC might transport Gqα from the cell body to the rhabdomere.…”
Section: Translocation Of Gqα Is Not Regulated By Shiberemediated Endmentioning
confidence: 99%